Drug-Drug/Drug-Excipient Compatibility Studies on Curcumin using Non-Thermal Methods - Moorthi Chidambaram; Kathiresan Krishnasamy (Tabriz University of Medical Sciences, 2014)
Purpose: Curcumin is a hydrophobic polyphenol isolated from dried rhizome of turmeric. Clinical usefulness of curcumin in the treatment of cancer is limited due to poor aqueous solubility, hydrolytic degradation, metabolism, and poor oral bioavailability. To overcome these limitations, we proposed to fabricate curcumin-piperine, curcumin-quercetin and curcumin-silibinin loaded polymeric nanoformulation. However, unfavourable combinations of drug-drug and drug-excipient may result in interaction and rises the safety concern. Hence, the present study was aimed to assess the interaction of curcumin with excipients used in nanoformulations. Methods: Isothermal stress testing method was used to assess the compatibility of drug-drug/drug-excipient. Results: The combination of curcumin-piperine, curcumin-quercetin, curcumin-silibinin and the combination of other excipients with curcumin, piperine, quercetin and silibinin have not shown any significant physical and chemical instability. Conclusion: The study concludes that the curcumin, piperine, quercetin and silibinin is compatible with each other and with other excipients.